Journal of Econometric Methods (De Gruyter, 2011)
The Journal of Econometric Methods aims to bridge the widening gap between econometric research and empirical practice. It publishes papers from top scholars in all areas of econometrics that consider a topic of broad interest to practitioners and are written in a style that is targeted at practitioners.